Kepemimpinan Gembala: Mewujudkan Spirit Kepemimpinan Yesus dalam Komunitas Religius - Yosef Masan Toron (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
Leadership is always understood as human capability to influence a person or groups to get certain goals. Stoner defines leadership as a process of directing or influencing groups or organizations to realize visions or goals. Being conscious of this importance of leadership, Ruteng Diocese, in the process of implementing the fifth year of the Third Sinode of Ruteng Diocese, invites all the chirstians, the leaders and congregations to reflect the theme of leadership of shepherds. All leaders in different levels, religious or layman, are invited and motivated to implement the leadership of the shepherd. For religious leaders, the theme chosen indicates not only a reality of misleading leadership in religious life but also guiding and motivating the implementation of the leadership in the spirit of Jesus, the Lord in the religious communities life.